1997
DOI: 10.1002/(sici)1097-4644(19971101)67:2<201::aid-jcb5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced utilization of Man5GlcNAc2-P-P-lipid in a Lec9 mutant of Chinese hamster ovary cells: Analysis of the steps in oligosaccharide-lipid assembly

Abstract: Recently we reported that CHB11-1-3, a Chinese hamster ovary cell mutant defective in glycosylation of asparagine-linked proteins, is defective in the synthesis of dolichol [Quellhorst et al., 343:19-26, 1997: Arch Biochem Biophys]. CHB11-1-3 was found to be in the Lec9 complementation group, which synthesizes polyprenol rather than dolichol. In this paper, levels of various polyprenyl derivatives in CHB11-1-3 are compared to levels of the corresponding dolichyl derivatives in parental cells. CHB11-1-3 was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…When the conversion of polyprenol to polyprenal is defective, dolichol can be replaced by polyprenol as intermediate oligosaccharide acceptor, with polyprenol being much poorer in this respect than dolichol for several of the reactions necessary for N-glycosylation. 35 , 36 , 37 , 38 , 39 We wondered whether an increase of polyprenol-phosphate (Pol-P) or polyprenol-phospho-hexoses (Pol-P-Hex) could cause the glycosylation defect observed in DHRSX-deficient cells ( Figure 1 L).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the conversion of polyprenol to polyprenal is defective, dolichol can be replaced by polyprenol as intermediate oligosaccharide acceptor, with polyprenol being much poorer in this respect than dolichol for several of the reactions necessary for N-glycosylation. 35 , 36 , 37 , 38 , 39 We wondered whether an increase of polyprenol-phosphate (Pol-P) or polyprenol-phospho-hexoses (Pol-P-Hex) could cause the glycosylation defect observed in DHRSX-deficient cells ( Figure 1 L).…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that polyprenol can be phosphorylated in cells and that the imbalance between polyprenol-P-hexose and dolichol-P-hexose might be the cause of the glycosylation defect in DHRSX and SRD5A3-deficient cells. 35 , 38
Figure 6 Accumulation of phospho- and phosphohexose-polyprenol alongside truncated N-linked oligosaccharide species in DHRSX/SRD5A3-deficient cells (A–D) Dolichol-phosphate or polyprenol-phosphate (A and C), and dolichol-phospho-hexose or polyprenol-phospho-hexose (B and D) were measured in wild-type, DHRSX KO, and SRD5A3 KO HAP1 cells and their respective complementations (A and B), as well as EBV-immortalized lymphoblasts from controls, patients, and parents (C and D). Data are TIC-normalized AUC (means ± SEM, n = 4; ∗ p < 0.05; ∗∗∗∗ p < 0.0001; § p < 0.05 compared to every control; # p < 0.05 compared to one of the controls).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on human cell lines show that DHRSX deficiency leads to a decrease in dolichol and an increase in polyprenol, and similar changes in glycosylation to those previously observed with Lec5 and Lec9 cells (18). In particular, previous work on the glycosylation defect in CHO Lec5 and Lec9 cells showed that the conversion of polyprenol to dolichol is deficient (16, 19). As a result of this, N-glycan synthesis in Lec5 and Lec9 cells utilizes polyprenol-phosphate rather than dolichol-phosphate species, leading to perturbation in the synthesis and transfer of the LLO ( Fig.…”
Section: Resultsmentioning
confidence: 99%